Defect‐Rich Porous Palladium Metallene for Enhanced Alkaline Oxygen Reduction Electrocatalysis - Yu, Hongjie; Zhou, Tongqing; Wang, Ziqiang; Xu, You; Li, Xiaonian; Wang, Liang; Wang, Hongjing (Angewandte Chemie International Edition, 2021)
Metallene with fantastic physicochemical properties is considered as a potential candidate for oxygen reduction reaction (ORR). Controlling the morphology and structure of metallene can provide a great opportunity to improve its catalytic performance. Herein, defect‐rich ultrathin porous Pd metallene (a sub‐nanometer and curved metal nanosheet) is developed by facile wet‐chemistry strategy for efficient and stable ORR electrocatalysis in alkaline electrolyte. The defect‐rich porous Pd metallene provides abundant highly active sites and vacancy defects, showing superior ORR activity of 0.892 A mgPd−1 at 0.9 V vs. the reversible hydrogen electrode. The mass activity is 5.1 and 16.8 times higher than those of commercial Pt/C and Pd/C, respectively, and maintains well after 5000 cycles. The strain effect and tunable electronic structure derived from highly curved sub‐nanometer nanosheet morphology contribute to the excellent ORR performance by the optimization of oxygen binding ability on Pd. The superior catalytic performance of Pd metallene may open an avenue to design other metallene materials for various fields. Ultrathin porous Pd metallene with rich nanocrystal defects were prepared by a one‐pot wet‐chemical method for superior oxygen reduction reaction performance in alkaline electrolytes.